2014
DOI: 10.1002/zoo.21148
|View full text |Cite
|
Sign up to set email alerts
|

Early development and growth in captive‐born Iberian lynx (Lynx pardinus)

Abstract: Knowledge on the growth and early development patterns of endangered species can become a useful conservation tool because it may allow detecting anomalous growth in newborns, both in captivity breeding and in the wild. We studied the growth and early development of 40 Iberian lynx (Lynx pardinus) cubs belonging to 21 litters born in captivity between 2005 and 2012 at "El Acebuche" Iberian Lynx Breeding Centre. This is the first study on growth in this critically endangered species. The Iberian lynx cubs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…The Iberian lynx is a semialtricial species whose young are born with poorly developed sensory 97 and locomotor systems (Yerga et al, 2014). The pattern of circadian activity is not usually 98 present in altricial species at birth (Ibuka, 1984, Kowalska et al, 2010.…”
mentioning
confidence: 99%
“…The Iberian lynx is a semialtricial species whose young are born with poorly developed sensory 97 and locomotor systems (Yerga et al, 2014). The pattern of circadian activity is not usually 98 present in altricial species at birth (Ibuka, 1984, Kowalska et al, 2010.…”
mentioning
confidence: 99%
“…The video‐surveillance system did not allow the correct individual identification of cubs by the pattern of spots during the first month of life because they are born covered with a uniform gray, downy fur without the typical spots of the species [Yerga et al, ], so the cubs had to be marked with a dye (Nyanzol D Powder®, Greenville Colorants, L.L.C., Jersey City, NJ). The marking was performed at 3 weeks of life to prevent disturbances to the mother and reduce the probability of abandoning the cubs.…”
Section: Methodsmentioning
confidence: 99%
“…Mean litter size is three but could range from one to four [Fernández and Palomares, ]. Kittens are semi‐altricial [Yerga et al, ]. They are born with the body covered with downy fur, with the senses of hearing and sight undeveloped and unable to walk.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of heavy females producing heavy offspring has been documented in reindeer [Rognmo et al, 1983;Skogland, 1984], fallow deer [Birgersson and Ekvall, 1997], sheep [Burfening and Carpio, 1993], and cattle [Ali, 2014]. External factors, such as calving season [Yilmaz et al, 2007;Ismail et al, 2011], year of birth [Shahzad et al, 2010;Yilmaz et al, 2013;Hussain et al, 2014], quality of food [Yerga et al, 2014], time spent feeding [Lavigueur and Barrette, 1992], and habitat [Leberg et al, 1992] have also been shown to influence the weight and growth of animals.…”
Section: Introductionmentioning
confidence: 99%
“…The body mass growth pattern in mammals follows a non-linear sigmoidal curve [Zullinger et al, 1984], with a point of inflection at about one-third of the final weight [von Bertalanffy, 1957]. The inflection point of growth, marking its slow-down [Walford, 1946], usually occurs when the young/juveniles start to feed by themselves [Portier et al, 2000;Yerga et al, 2014].…”
Section: Introductionmentioning
confidence: 99%